ETHICAL PERCEPTIONS OF TAX ACCOUNTING AND LOGISTICS ADMINISTRATION MANAGEMENT STUDENTS TOWARDS TAX EVASION - Zafira, Hanifah; Muid, Dul; Wardhani, Dian Kusuma (Tax Accounting Applied Journal, 2023)
This study observed the perceptions of tax accounting and logistics administration management students at the Diponegoro University Vocational School. These two groups of respondents were compared to find out if their perceptions of tax evasion differed as measured using perspectives on tax justice, tax system, and discrimination. This study used a survey method of respondents. The sampling method in this survey is purposive sampling. The analytical methods used for this study were pearson correlation for validity, cronbach alpha for reliability, one sample Kolmogorov-Smirnov for normality, and independent sample T-test for hypothesis testing. The results of this study show that there are differences in ethical perceptions of tax accounting and logistics administration management students towards tax evasion. Based on the average analysis, tax accounting students are more opposed to tax evasion than logistics administration management students. According to the perception of tax accounting students, tax evasion is unethical to do, while the perception of logistics management students they still doubt whether tax evasion is ethical to do or not.